A Member of the 14-3-3 Gene Family in Brachypodium distachyon, BdGF14d, Confers Salt Tolerance in Transgenic Tobacco Plants - He, Yuan; Zhang, Yang; Chen, Lihong; Wu, Chunlai; Luo, Qingchen; Zhang, Fan; Wei, Qiuhui; Li, Kexiu; Chang, Junli; Yang, Guangxiao; He, Guangyuan (Frontiers in Plant Science, 2017)
Plant 14-3-3 proteins are involved in diverse biological processes, but for the model monocotyledonous species, Brachypodium distachyon, their roles in abiotic stress tolerance are not well understood. In this study, a total of eight Bd14-3-3 genes were identified from B. distachyon and these were designated respectively as BdGF14a-BdGF14g. The qRT-PCR analyses of 3-month-old plants of B. distachyon showed that these genes were all expressed in the stems, leaves, and spikelets. By contrast, most of the plants had relatively lower transcriptional levels in their roots, except for the BdGF14g gene. The different expression profiles of the Bd14-3-3s under various stress treatments, and the diverse interaction patterns between Bd14-3-3s and BdAREB/ABFs, suggested that these gene products probably had a range of functions in the stress responses. The NaCl-induced Bd14-3-3 gene, BdGF14d, was selected for overexpression in tobacco. BdGF14d was found to be localized throughout the cell and it conferred enhanced tolerance to salt in the transgenic plants. Lowered contents of malonaldehyde (MDA), H2O2, and Na+, and lower relative electronic conductance (Rec%), yet greater activities of catalase (CAT) and peroxidase (POD), were observed in the overexpressing plants. Higher photosynthetic rate, transpiration rate, stomatal conductance, and water use efficiency (WUE) were measured in the transgenic lines. Following abscisic acid (ABA) or NaCl treatment, stomatal aperture in leaves of the BdGF14d-overexpression plants was significantly lower than in leaves of the wild type (WT) controls. The stress-related marker genes involved in the ABA signaling pathway, the reactive oxygen species (ROS)-scavenging system, and the ion transporters were all up-regulated in the BdGF14d-overexpressing plants as compared with WT. Taken together, these results demonstrate that the Bd14-3-3 genes play important roles in abiotic stress tolerance. The ABA signaling pathway, the ROS-scavenging system, and ion transporters were all involved in enhancing the tolerance to salt stress in the BdGF14d-overexpression plants